Perspektif Masyarakat dalam Pertimbangannya Memilih Bank Syariah Indonesia Di Kantor Cabang 1 Kota Palangka Raya (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The development of Islamic banking in Indonesia has shown significant growth, accompanied by increasing public awareness in selecting financial services that comply with Sharia principles. This study aims to analyze community perspectives in their considerations when choosing Bank Syariah Indonesia, Branch Office 1 in Palangka Raya. A qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. The findings indicate that the community’s decision to choose Bank Syariah Indonesia is not solely influenced by religiosity, but also by service quality, ease of product access, institutional trust, and social influences. Savings products such as Easy Wadi’ah Savings and Easy Mudharabah Savings are the most preferred, as they are perceived to be flexible, user-friendly, and suitable for daily transaction needs. Furthermore, the role of human resources in providing effective education and high-quality services contributes significantly to strengthening positive public perceptions of Islamic banking. The study reveals that community perspectives in selecting Bank Syariah Indonesia are multidimensional, integrating both religious and rational considerations. Therefore, enhancing the competitiveness of Islamic banking requires the integration of Sharia values with continuous improvements in service quality.